Fatigue life reassessment of monopile-supported offshore wind turbine structures - Petrovska, Elize (The University of Edinburgh, 2023)
The UK has seen a rapid growth of the offshore wind industry over the past two decades, from a single 4MW project commissioned in 2000 to more than 11GW installed capacity in the UK waters by 2022. The majority of existing (and projected near future) offshore wind turbines (OWTs) are supported by fixedbottom monopile foundations. Operational experience to date has highlighted the long-term structural integrity of the foundations as one of the key Operations & Maintenance challenges. This is due to high levels of uncertainty caused by stochastic through-life variations in site environmental conditions, as well as their influence on the remaining operational life and end-of-life decision making regarding OWT assets. However, the re-evaluation of structural integrity during operations is complicated by a lack of established standards or industry best practice, leading to inconsistent and potentially expensive assessment processes. This thesis investigates the methodologies for structural lifetime reassessment of monopile-supported OWTs based on the operational knowledge obtained from site monitoring, design information and numerical modelling, and applies them to a Round 1 offshore wind farm to illustrate their potential and shortcomings. The data-centric part of the work presents a detailed analysis of strain monitoring data, coupled with operational and environmental measurements, towards a data-based fatigue life reassessment. The work highlights a significant extent of overdesign and quantifies the remaining structural reserves of the wind turbine for various operational scenarios to be in excess of 100 years. The numerical modelling part of this research comprises development of a corresponding turbine-specific numerical model to predict the remaining useful life, coupled with a sensitivity analysis to highlight the variables that cause the highest variability in fatigue life. Structural parameters such as damping and corrosion, as well as environmental load uncertainties in wind speed, turbulence and wave ...